Supplementary Feeding (PMT) For Pregnant Women with SEVERITY - Maria Ulfah, Sofia; Yulianti, Syami; Aprian Astuti, Rima; Agustina, Yenila; Yunila, Tri; Hartati Saragih, Sri (Universitas Dehasen Bengkulu, 2024)
Supplementary Feeding (PMT) for Pregnant Women with Chronic Energy Deficiency (CED) is an effort to address serious nutritional issues in Indonesia. CED in pregnant women can lead to long-term health impacts on both the mother and the unborn child. This study aims to provide a concrete solution by implementing PMT directly for pregnant women with CED in Kesambe Lama Village, Rejang Lebong District, Bengkulu Province. The problem-solving methods include screening, counseling, and the provision of supplementary food integrated into community service activities. The results achieved show a significant improvement in the understanding of pregnant women about the importance of nutritional intake, as well as positive changes in their nutritional status. The conclusion of this activity is that PMT is effective in improving the health of pregnant women with CED and should be continued and expanded to other areas facing similar issues.